Toward a better understanding of adult dual use of cigarettes and e-cigarettes based on use intensity and reasons for dual use. (February 2023) - Lee, Shin Hyung; Han, Dae-Hee; Seo, Dong-Chul
Highlights: To help quit smoking and stealth vaping are two reasons for using e-cigarettes have been predominantly reported from adult dual users of cigarettes and e-cigarettes. Dual use status based on daily use intensity of cigarettes and e-cigarettes was significantly associated with the two reasons for using e-cigarettes. A different pattern of dual use behaviors by different age groups was found. There are significant associations between e-cigarette device characteristics and the two reasons for using e-cigarettes. Abstract: Background: Dual use of combustible cigarettes and e-cigarettes is an emerging phenomenon among U.S. adults. Literature suggests two primary reasons for this emerging use (i.e., to help quit smoking and to stealth vape). This study investigated user profiles based on use intensity and the reasons for dual use. Methods: A total of 1, 151 U.S. adult dual users were drawn from the 2018–2019 Tobacco Use Supplement to the Current Population Survey. We divided them into four groups: daily dual users (n = 189), predominant smokers (n = 608), predominant vapers (n = 143), and non-daily dual users (n = 211). We performed weighted multivariable logistic regressions to identify factors associated with the two primary reasons for dual use. Results: 3 in 10 of U.S. adult dual users used e-cigarettes to help quit smoking while 2 in 10 of U.S. adult dual users used e-cigarettes to stealth vape. Compared to daily dual users, predominant smokers [adjusted odds ratio (AOR) = 0.61, 95% CI = 0.23, 0.62] were less likely to use e-cigarettes to help quit smoking whereas predominant vapers (AOR = 1.80, 95% CI = 1.04, 3.13) were more likely to use e-cigarettes to help quit smoking and less likely to use e-cigarettes to stealth vape (AOR = 0.30, 95% CI = 0.10, 0.89). Conclusions: There was notable heterogeneity among the four groups of dual users. As the landscape of tobacco use is rapidly changing with an increasing popularity of e-cigarettes, reasons as well as behaviors of dual users need to be regularly monitored for effective tobacco control.